До семантики центральноїсценипекторалі з Товстої Могили - Бабенко, Л. І. (Давнина. Харківський історико-археологічний щорічник)
Резюме Бабенко Л. И. О семантике композиции пекторали из Толстой Могилы Трактовка семантики центральной сцены верхнего фриза пекторали из Толстой Могилы отличается наибольшим разнообразием мнений. Дополнительную информацию для решения этой проблемы можно извлечь из композиционного строения самой пекторали и заложенных в ней числовых структур. Дисбаланс между количеством смертей на нижнем фризе (семь) и рождений на верхнем (шесть) дает основание для толкования доминирующего смысла центральной сцены как также содержащего в себе идею рождения, т. е., седьмого по счету. Символика числа семь воплощена в композиции пекторали и посредством семи фигурок птиц, а также в семичастной структуре самой пекторали, состоящей из четырех витых жгутов и трех орнаментальных фризов между ними. При решении проблемы идентификации персонажей центральной сцены необходимо учитывать характер пекторали как личного украшения и участие ее владельца-носителя, который и был центральным персонажем всей композиции пекторали. Ключевые слова: пектораль, скифы, фарн, руно, Толстая Могила. Summary L. Babenko. About the Pectoral From Tolstaya Mohyla composition semantics The semantics interpretation of the upper frieze central scene of the pectoral from Tolstaya Mohyla is famous for the greatest variety of opinions. The optional information for this problem solving can be found in the compositional constitution of the pectoral and the numeric structures in it. The imbalance of the death quantity in the lower frieze (seven) and the birth quantity in the upper one gives ground for interpreting the dominant sense of the central part as containing the birth idea, and also being the seventh. The symbolism of the number seven is represented in the pectoral composition through the seven bird figures, as well as in the seven-part structure of the pectoral itself, which is composed of four twisted plaits and three ornamental friezes between them. When solving the identification problem of the central scene characters it is necessary to take into consideration the type of the pectoral as of a personal adornment and the participation of its owner who was the central character of the whole pectoral composition. Key words: pectoral, Scythians, Farn, fleece, Tolstaya Mohyla.